Hf-W chronology of ordinary chondrites. (1st August 2019) - Hellmann, Jan L.; Kruijer, Thomas S.; Van Orman, James A.; Metzler, Knut; Kleine, Thorsten
Abstract: Fifteen H, L, and LL ordinary chondrites of petrologic types 4–6 have been analyzed for Hf-W isotope systematics to constrain the chronology, internal structure, and thermal history of their parent bodies. For most samples coarse-grained metals plot below the isochrons defined by silicate-dominated fractions which consist of variable mixtures of silicate minerals with tiny metal inclusions. This offset results from an earlier Hf-W closure in the large metal grains and provides a new means for simultaneously determining cooling rates and Hf-W closure ages for individual samples. For most type 5 and 6 samples, cooling rates and Hf-W ages are inversely correlated, indicating that these samples derive from concentrically zoned bodies in which more strongly metamorphosed samples derive from greater depth. These data, therefore, provide strong evidence for a common 'onion shell' structure for the H, L, and LL chondrite parent bodies. The cooling rates and Hf-W ages of some type 5 and 6 chondrites overlap, indicating that the Hf-W systematics provide a more robust measure of the thermal history and burial depth of a given sample than the simple petrographic distinction between types 5 and 6. Two type 6 samples deviate from the correlation between cooling rates and Hf-W ages and cooled much faster than expected for their Hf-W age. These samples likely were excavated by impacts that occurred during high-temperature metamorphism and prior to complete closure of the Hf-W system at ∼10 Ma after CAI formation. As these impacts would have disturbed the asteroid's cooling history, these samples likely derive from different bodies than samples with undisturbed cooling histories, implying that ordinary chondrites derive from more than just three parent bodies. The Hf-W data reveal that metal-silicate fractionation among the H, L, and LL groups occurred between ∼2 and ∼2.7 Ma after CAI formation and, hence, was about coeval to chondrule formation. As both metal-silicate fractionation and chondrule formation occurred prior to chondrite parent body accretion, there should be no ordinary chondrite chondrules that are younger than ∼2.7 Ma. Finally, ordinary chondrite precursors had lower Hf/W ratios than carbonaceous chondrites, suggesting that inner and outer solar system materials, respectively, were chemically distinct even for refractory elements.